Peran Pemerintah Daerah Dalam Penyediaan Air Bersih di Kelurahan Untia Kecamatan Biringkanaya Kota Makassar - Nurul Alfiani (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
Clean water is water used for daily needs whose quality meets health requirements and can be drunk when it has been cooked. Clean water that is healthy and of good quality and continuously flowing is really needed by the community because it can improve the quality of people's lives. The purpose of this study is to determine the role of the government in providing clean water and the factors that influence the provision of clean water. This research uses a qualitative approach with descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation methods. The data obtained were then analyzed through several stages, namely data reduction, data presentation, and conclusion drawing. The results obtained show that the Public Works Office as one of the local government instruments in providing clean water has role indicators, namely (1) planning activities in the field of clean water, (2) implementing activities in the field of clean water, (3) distributing tasks and controlling the implementation of activities in the field of clean water. From these indicators, it is found that the implementation of the role of the Public Works Office is still not optimal. This is based on the condition of the Untia Village area which is located in a coastal area so that the provision of clean water through the drilling system is still difficult to obtain clean water. Based on the analysis of primary and secondary data, the researcher identified several solutions that can encourage the success of clean water supply, namely providing clean water infrastructure in the form of tools or machines that can reduce underground salt levels for coastal areas, collaborating with clean water supply agencies, and making a master plan for clean water supply that is more planned and integrated.